A study on the influence of cross-sectional shapes and convolutions on PVDF fiber properties. Issue 5 (4th May 2023) - Wang, Jie; Fu, Chiyu; Duan, Xiangyu; Liu, Jiaxin; Xia, Zhigang
Abstract: Polyvinylidene fluoride (PVDF) is a piezoelectric polymer for the potential massive production of smart textiles, facing the difficulty of synergetic improving its fiber strength and softness. Strengthening of flexible PVDF fibers via drawing incurs the reduction of fiber softness. Here, inspired by the cotton fibers, this study aimed to construct a strong and soft PVDF fiber by regulating its cross-sectional shape and longitudinal convolution. Mechanism of increasing softness by longitudinal spiral twisting was conducted during the strengthening of PVDF fibers with favorable cross-sectional shapes. Then circular, flat and kidney shaped PVDF fibers were prepared to conduct drawing and twisting under different parameters. The influences of cross-sectional shapes and convolutions on PVDF fiber properties were examined using scanning electron microscope (SEM), X ray diffraction (XRD), universal stretch meter and AFM. Results indicated that all the fibers became strong but rigid with increased drawing ratios, mainly due to their corresponding attenuation to increase fiber inner crystallization and surface smoothness. In specialty, the circular fiber had a higher crystallization increase ratio (106.3%) than that of kidney (74.7%) and flat (73.1%) fibers. Surprisingly, all drawn fibers became flexible and further strengthened after tensile twisting within 400 T/m. Overall the optimum strong and flexible fibers were obtained by 400 T/m tensile twisting of the 2 times drawn flat PVDF fibers.